Clinical and epidemiological features of definitive and presumed loxoscelism in São Paulo, Brazil - Ceila Maria Sant'Ana MÁLAQUE; Jaime Enrique CASTRO-VALENCIA; João Luiz Costa CARDOSO; Francisco Oscar de Siqueira FRANÇA; Kátia Cristina BARBARO; Wen FAN Hui (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
A retrospective study analysed 359 proven or presume cases of loxoscelism seen at the Hospital Vital Brazil, Instituto Butantan, São Paulo, Brazil, between 1985 and 1996. The spider was identified in 14%. The bites occurred predominantly in the urban areas (73%) between September and February. Patients > 14 years were commonest inflicted (92%) and 41% were bitten while getting dressed. Only 11% sought medical care within the first 12 hours post bite. Cutaneous loxoscelism was the commonest form presenting (96%); commonest manifestations were: pain (76%), erythema (72%), edema with enduration (66%), ecchymosis (39%). Skin necrosis occurred in 53% of patients, most frequently seen on trunk, tigh and upper arm, and when patients seek medical care more than 72 hours after bite. Local infection was detected in 12 patients (3%). Hemolysis was confirmed in 4 cases (1.1%). Generalised cutaneous rash, fever and headache were also observed in 48% of the total of patients. None of them had acute renal failure or died. Treatment usually involved antivenom administration (66%), being associated with corticosteroids (47%) or dapsone (30%). Presumptive diagnosis of loxoscelism may be established based on clinical and epidemiological findings. Further investigations are required to prove the value of antivenom and other treatment schedules.